Treatment-Free Remission in Chronic Myeloid Leukemia and New Approaches by Targeting Leukemia Stem Cells - Chen, Yilin; Zou, Jing; Cheng, Fanjun; Li, Weiming (Frontiers in Oncology, 2021)
The therapeutic landscape for chronic myeloid leukemia (CML) has improved significantly with the approval of tyrosine kinase inhibitors (TKIs) for therapeutic use. Most patients with optimal responses to TKIs can have a normal life expectancy. Treatment-free remission (TFR) after discontinuing TKI has increasingly become a new goal for CML treatment. However, TKI only “control“ CML, and relapse after discontinuation has become a key factor hindering patient access to attempt TFR. In this study, we reviewed studies on TKI discontinuation, including both first and second-generation TKI. We also reviewed predictors of relapse, new monitoring methods, and strategies targeting leukemic stem cells.